Combating the crime of financing terrorism in Algerian legislation - SI NACER, Mohamed; GUERIBIZ, Mourad (Journal of Human Sciences, 2020)
The crime of financing terrorism is a dual criminalization crime, the crime of financing and the crime of terrorism, therefore it is one of the most dangerous crimes developed and a form of evolving crime that the international community has addressed by combating and criminalizing through international conventions, including the International Convention for the Suppression of the Financing of Terrorism in 1999 that began to criminalize the financing of terrorism and has urged many countries to harmonize its legislation International agreements have developed Algeria from its legislation to criminalize the fight against the financing of terrorism. Through this research paper, we wanted to explain how the Algerian legislator responded to terrorist acts.